Un vislumbre de lucidez: Interpretación fenomenológica del instante kierkegaardiano - Garrido Maturano, Ángel Enrique (2017)
The article attempts a phenomenological and hermeneutical analysis of Kierkegaard’s notion of instant conceived as the synthesis of time and eternity from an anthropological and existential viewpoint. It first shows the concrete instant as a correlation between the absolute meaning freely assumed for his existence by a subject and an event by virtue of which the sum total of what he is demands a decision in favor of that meaning as a means to catch a glimpse of the absolute and eternal in time. Secondly, the article explains how the instant requires a conjunction of faith and wisdom, which is termed lucidity, in order to make itself concrete.